Association between hypertensive disorders of pregnancy and later risk of cardiovascular outcomes - Oliver-Williams, Clare; Stevens, David; Payne, Rupert A.; Wilkinson, Ian B.; Smith, Gordon C. S.; Wood, Angela (BMC medicine, 2022)
Background Hypertensive disorders of pregnancy are common pregnancy complications that are associated with greater cardiovascular disease risk for mothers. However, risk of cardiovascular disease subtypes associated with gestational hypertension or pre-eclampsia is unclear. The present study aims to compare the risk of cardiovascular disease outcomes for women with and without a history of gestational hypertension and pre-eclampsia using national hospital admissions data. Methods This was a retrospective cohort study of national medical records from all National Health Service hospitals in England. Women who had one or more singleton live births in England between 1997 and 2015 were included in the analysis. Risk of total cardiovascular disease and 19 pre-specified cardiovascular disease subtypes, including stroke, coronary heart disease, cardiomyopathy and peripheral arterial disease, was calculated separately for women with a history of gestational hypertension and pre-eclampsia compared to normotensive pregnancies. Results Amongst 2,359,386 first live births, there were 85,277 and 74,542 hospital admissions with a diagnosis of gestational hypertension and pre-eclampsia, respectively. During 18 years (16,309,386 person-years) of follow-up, the number and incidence of total CVD for normotensive women, women with prior gestational hypertension and women with prior pre-eclampsia were n = 8668, 57.1 (95% CI: 55.9–58.3) per 100,000 person-years; n = 521, 85.8 (78.6–93.5) per 100,000 person-years; and n = 518, 99.3 (90.9–108.2) per 100,000 person-years, respectively. Adjusted HRs (aHR) for total CVD were aHR (95% CI) = 1.45 (1.33–1.59) for women with prior gestational hypertension and aHR = 1.62 (1.48–1.78) for women with prior pre-eclampsia. Gestational hypertension was strongly associated with dilated cardiomyopathy, aHR = 2.85 (1.67–4.86), and unstable angina, aHR = 1.92 (1.33–2.77). Pre-eclampsia was strongly associated with hypertrophic cardiomyopathy, aHR = 3.27 (1.49–7.19), and acute myocardial infarction, aHR = 2.46 (1.72–3.53). Associations were broadly homogenous across cardiovascular disease subtypes and increased with a greater number of affected pregnancies. Conclusions Women with either previous gestational hypertension or pre-eclampsia are at greater risk of a range of cardiovascular outcomes. These women may benefit from clinical risk assessment or early interventions to mitigate their greater risk of various cardiovascular outcomes.